2006
DOI: 10.1590/s0102-33062006000100022
|View full text |Cite
|
Sign up to set email alerts
|

Micromorfologia da superfície do fruto de espécies de Mikania Willd. (Asteraceae) ocorrentes no estado do Rio Grande do Sul, Brasil

Abstract: Brazil). This work presents the surface micromorphology of fruits of 15 taxa of Mikania Willd. studied under scanning electron microscopy (SEM). The aim was to find characters to separate close species that occur in Rio Grande do Sul State. Such characters had taxonomic value for some of them. The species were separated into four groups according to the pattern. The pattern with striated periclinal and anticlinal walls with verrucose projections was the most constant in the species of Mikania Willd. analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
14

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 10 publications
0
9
0
14
Order By: Relevance
“…Para o Brasil são aceitas 203 espécies (Ritter et al, 2015), sendo queas mais utilizadas na medicina popular para tratamento das afecções respiratórias são Mikania glomerata Spreng. e M. laevigata Sch.…”
Section: Introductionunclassified
“…Para o Brasil são aceitas 203 espécies (Ritter et al, 2015), sendo queas mais utilizadas na medicina popular para tratamento das afecções respiratórias são Mikania glomerata Spreng. e M. laevigata Sch.…”
Section: Introductionunclassified
“…Among the Asteraceae of the cerrado vegetation studied by Castro et al (1997), type IV trichomes (glandular and uniseriate with peduncle composed of from six to seven cells and unicellular secretory portion) occurred exclusively between the Eupatorieae and Heliantheae (sensu Bremer 1994). In their study of the micromorphology of species of Mikania, Ritter and Miotto (2006) reported that some simple, pluricellular and uniseriate trichomes, as well as many glandular trichomes, were observed on the surface of the fruits of M. micrantha. However, type IV trichomes that are found in the present examination of this species were not reported by those authors.…”
Section: Discussionmentioning
confidence: 99%
“…Wagenitz (1976) suggested that anatomical studies of the fruits of the Asteraceae might aid in elucidating its systematics. Characteristics of the indumentum (Ritter and Miotto 2006), pappus (Bean 2001), carpopodium (Haque and Godward 1984), and the anatomy of the pericarp itself (Bruhl and Quinn 1990), or a com-bination of all of the characters cited above (Leszek et al 1997), have been used to delimit tribes, genera, and even species of this family.…”
Section: Introductionmentioning
confidence: 99%
“…No Brasil, ocorre de norte a sul, tendo sua principal área de dispersão nos estados de Minas Gerais, Rio de Janeiro e São Paulo (Oliveira, 1972;Ritter & Miotto, 2005). M. glomerata Sprengel é uma planta medicinal bastante empregada na medicina popular devido as suas propriedades broncodilatadora, antiasmática, expectorante e antitussígena (Panizza, 1997).…”
Section: Introductionunclassified